Proceedings of the 1st ACM SIGCHI Symposium on Engineering Interactive Computing Systems 2009
DOI: 10.1145/1570433.1570473
|View full text |Cite
|
Sign up to set email alerts
|

A formal approach supporting the comparative predictive assessment of the interruption-tolerance of interactive systems

Abstract: This paper presents an approach for investigating in a predictive way potential disruptive effects of interruptions on task performance in a multitasking environment. The approach combines previous work in the field of interruption analysis, formal description techniques for interactive systems and stochastic processes to support performance analysis of user activities constrained by the occurrence of interruptions. The approach uses formal description techniques to provide a precise description of user tasks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…set of states represented in intention in Petri nets while represented in extension in an automata). (Palanque et al 2009) Formal verification involves techniques that are strongly rooted in mathematics. Defects in models can be detected by formal verification.…”
Section: Verification and Validationmentioning
confidence: 99%
“…set of states represented in intention in Petri nets while represented in extension in an automata). (Palanque et al 2009) Formal verification involves techniques that are strongly rooted in mathematics. Defects in models can be detected by formal verification.…”
Section: Verification and Validationmentioning
confidence: 99%
“…He then experimented with sensors to evaluate a person's personal and social interruptability and achieved a 98.1% recognition score for social interruptability. Palanque et al [25] analyzed interruptions using model-based analytical techniques that could be used in designing interruption-tolerant systems. To demonstrate, the authors used a case study to compare two interaction techniques, Speak and Drop and Drag and Drop, and found the latter was more resistant to interruptions.…”
Section: Coordinating Interruptionsmentioning
confidence: 99%
“…Notwithstanding, there are some situations where the interruption of present task can be predicted -in particular when users decided to get interrupted -, so that the systems should provide an alternative representation of the interrupted tasks. Only a few works in the literature have addressed the description of interruptions in system specifications [14]. It is interesting to notice that despite the fact that modelbased approaches [15] are prominent in the field of Web engineering, as far as we could investigate there is no clear proposal for using Model-Driven Approaches for building Web sites resilient to interruptions.…”
Section: Model-based Approach For Dealing With Interruptionsmentioning
confidence: 99%
“…Formally speaking an interruption can be defined as a (intentional or unexpected) switch between two tasks; when an interruption occurs, users are forced to do something else (the secondary task) until the primary task can be resumed [19].It has also been shown that interruptions will ultimately affect users' ability to complete tasks but the disruptive effect varies according to the type of interruption (e.g. system alarms and notification, denial of service, loss of connectivi-ty…) [14]. Thus, there is no universal solution for dealing with interruptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation